Characterisation of Physical Frailty and Associated Physical and Functional Impairments in Mild Cognitive Impairment - Nyunt, Ma Shwe Zin; Soh, Chang Yuan; Gao, Qi; Gwee, Xinyi; Ling, Audrey S. L.; Lim, Wee Shiong; Lee, Tih Shih; Yap, Philip L. K.; Yap, Keng Bee; Ng, Tze Pin (Frontiers in Medicine, 2017)
Objective: To characterize the physical frailty phenotype and its associated physical and functional impairments in mild cognitive impairment (MCI). Method: Participants with MCI (N=119), Normal Low Cognition (NLC, N=138), and Normal High Cognition (NHC, N=1681) in the Singapore Longitudinal Ageing Studies (SLAS-2) were compared on the prevalence of physical frailty, low lean body mass, weakness, slow gait, exhaustion and low physical activity, and POMA balance and gait impairment and fall risk. Results: There were significantly higher prevalence of frailty in MCI (18.5%), than in NLC (8.0%) and NHC (3.9%), and pre-frailty in MCI (54.6%), NLC (52.9%) than in NHC (48.0%). Age, sex and ethnicity-adjusted OR (95% CI) of association with MCI (versus NHC) for frailty were 4.65 (2.40-9.04) and for pre-frailty, 1.67 (1.07-2.61). Similar significantly elevated prevalence and adjusted ORs of association with MCI were observed for frailty-associated physical and functional impairments. Further adjustment for education, marital status, living status, comorbidities, and GDS significantly reduced the OR estimates. However, the OR estimates remained elevated for frailty: 3.86 (1.83-8.17), low body mass: 1.70, (1.08-2.67), slow gait: 1.84 (1.17-2.89), impaired gait: 4.17 (1.98-8.81) and elevated fall risk (3.42 (1.22-9.53). Conclusion: Two thirds of MCI were physically frail or pre-frail, most uniquely due to low lean muscle mass, slow gait speed, or balance and gait impairment. The close associations of frailty and physical and functional impairment with MCI have important implications for improving diagnostic acuity of MCI and targeting interventions among cognitively frail individuals to prevent dementia and disability.